Neuroendocrine Tumors of the Pancreas: What's New - Dimou, Anastasios T; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Surgical excision has been the mainstay of treatment for neuroendocrine tumors of the pancreas (PNET). Compounds like streptozocin and dacarbazin have been traditionally used in inoperable cases and somatostatin to treat syndromes deriving from functional tumors. However, a lot of progress has taken place in the area of molecular characterization of these tumors, revealing activation of mammalian target of rapamycin (mTOR) and VEGF pathways. Recent data from the 2010 ASCO Gastrointestinal Cancers Symposium demonstrate antitumor activity of everolimus, an mTOR inhibitor in combination with temozolomide in a phase I/II trial and of sunitinib versus placebo in a randomized double blinded phase III trial. The role of modern biologic compounds in the treatment of PNET is not clear yet. In addition, combination of resection and transarterial chemoembolization (TACE) has been proven effective over either modality alone in the treatment of PNET metastatic to the liver in a retrospective analysis. This comes to address the problem of selecting local intervention in a metastatic disease, which has been a reasonable choice for this group of tumors in the past. Last but not least the role of Ki-67 in decision-making in PNET is being discussed. Image: Yale University School of Medicine. New Haven, CT, USA.